THE EFFECT OF GADJET ON ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) IN PRESCHOOL CHILDREN: LITERATUR REVIEW - Mega Vuriyanti; Iis Rahmawati; Suhari Suhari (UPT Penerbitan Universitas Jember, 2023)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a psychiatric disorder that often occurs in children and can persist into adolescence. This condition is characterized by inability to focus attention (inattention), hyperactivity and impulsivity. The cause of ADHD is still unclear, but it is suspected that the use of gadgets contributes to the occurrence of ADHD in preschool children. Objective: this research aim to analyze the effect of the use of gadgets on preschool children with ADHD. Methods: the chosen research methodology is literature review. All the data has matched the inclusion criteria and collected from online platforms such as PubMed, Scient Direct, and Google Scholar was published in 2019 - 2023. Results: of the 10 journals reviewed, it was stated that the use of gadgets had an effect on the occurrence of ADHD, 2 journals said that children with ADHD would have learning difficulties. Preschoolers with ADHD have a habit of playing gadgets for more than the recommended duration of one hour/day. Conclusion: the use of gadgets in preschool children affects the ADHD